Egetræet i vandglasset, pigen i egetræet - Linnea Ginman, Amanda (Peripeti, 2021)
The theatrical communication in Tim Crouch’s play An Oak Tree is analyzed in order to discuss the common conceptual characteristics between the play and Michael Craig-Martin’s installation piece of the same title. This perspective furthers an understanding of the theatrical communication that Crouch creates in An Oak Tree, showing how the audience allows the process of theatricality by using their own perception.